Synthesis of oxidative metabolites of CRA13 and their analogs: Identification of CRA13 active metabolites and analogs thereof with selective CB2R affinity - Hassan, Ahmed H. E.; Cho, Min Chang; Kim, Hye In; Yang, Ji Seul; Park, Kyung Tae; Hwang, Ji Young; Jang, Choon-Gon; Park, Ki Duk; Lee, Yong Sup (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
CRA13; a peripheral dual CB1R/CB2R agonist with clinically proven analgesic properties, infiltrates into CNS producing adverse effects due to central CB1R agonism. Such adverse effects might be circumvented by less lipophilic compounds with attenuated CB1R affinity. Metabolism produces less lipophilic metabolites that might be active metabolites. Some CRA13 oxidative metabolites and their analogues were synthesized as less lipophilic CRA13 analogues. Probing their CB1R and CB2R activity revealed the alcohol metabolite 8c as a more potent and more effective CB2R ligand with attenuated CB1R affinity relative to CRA13. Also, the alcohol analogue 8b and methyl ester 12a possessed enhanced CB2R affinity and reduced CB1R affinity. The CB2R binding affinity of alcohol analogue 8b was similar to CRA13 while that of methyl ester 12a was more potent. In silico study provided insights into the possible molecular interactions that might explain the difference in the elicited biological activity of these compounds.
Keywords: CANNABINOID RECEPTOR; ENDOCANNABINOID SYSTEM; MEDICAL CANNABIS; CB1; HYPERTENSION; MODULATION; AGONIST; TARGETS; RATS